From Kitsch and Carnivalesque to Cultural Appropriations: Liminal Representations of Post-Apartheid White Identity in Die Antwoord’s Music Videos - Dobrogoszcz, Tomasz (Text Matters: A Journal of Literature, Theory and Culture, 2024)
Through their multi-dimensional artistic performances—manifesting in music, lyrics and videos—the South African rap-rave hip-hop duo Die Antwoord expresses the ethos of “Zef,” a white working-class Afrikaner post-apartheid culture. Zef is associated with a specific style of vulgar aesthetics, language and humour which portrays its subjects in a derogatory manner, by presenting their appearance and behaviour as crudely ill-bred and vainly tasteless. This paper discusses discursive and visual strategies employed in selected Die Antwoord music videos, demonstrating how their use of kitsch aesthetics and carnivalesque elements allows them to render the liminality of contemporary white Afrikaans experience. It also examines the way in which the appropriation of cultural signifiers in the band’s work undermines myths of authenticity, represents the fragmentariness of subjectivity, and emphasizes the rhizomatic qualities of post-apartheid identity. The primary example will concern the band’s adaptation of Roger Ballen’s photographic work. Absorbing Ballen’s aesthetics is shown to be part of a broader artistic strategy of appropriation adopted by Die Antwoord with the view of attacking established social categories and destabilizing normativity. As the paper postulates, the band’s music videos employ liminal and carnivalesque artistic modes, combined with intertextual appropriations, in order to interrogate post-apartheid South African identity.